On The History of Boxing, the Origin and the Encouragement of Leather Gloves - Abdimurodovich, Choriyev Karim (European Journal of Life Safety and Stability (2660-9630), 2021)
The history of the sport of boxing and its prestige among the Olympic Games. About the role of boxing, one of the world's sports, in our country and the podium of Uzbek boys in the world. The first steps in professional boxing. Achievements in Uzbek sports Information about many victories.